Outer brain barriers in rat and human development - Brøchner, Christian B.; Holst, Camilla B.; Møllgård, Kjeld (Frontiers in Neuroscience, 2015)
Complex barriers at the brain’s surface, particularly in development, are poorly defined. In the adult, arachnoid blood-cerebrospinal fluid (CSF) barrier separates the fenestrated dural vessels from the CSF by means of a cell layer joined by tight junctions. Outer CSF-brain barrier provides diffusion restriction between brain and subarachnoid CSF through an initial radial glial end feet layer covered with a pial surface layer. To further characterize these interfaces we examined embryonic rat brains from E10 to P0 and forebrains from human embryos and fetuses (6th-21st weeks post conception) and adults using immunohistochemistry and confocal microscopy. Antibodies against claudin-11, BLBP, collagen 1, SSEA-4, MAP2, YKL-40, and its receptor IL-13Rα2 and EAAT1 were used to describe morphological characteristics and functional aspects of the outer brain barriers. Claudin-11 was a reliable marker of the arachnoid blood-CSF barrier. Collagen 1 delineated the subarachnoid space and stained pial surface layer. BLBP defined radial glial end feet layer and SSEA-4 and YKL-40 were present in both leptomeningeal cells and end feet layer, which transformed into glial limitans. IL-13Rα2 and EAAT1 were present in the end feet layer illustrating transporter/receptor presence in the outer CSF-brain barrier. MAP2 immunostaining in adult brain outlined the lower border of glia limitans; remnants of end feet were YKL-40 positive in some areas. We propose that outer brain barriers are composed of at least 3 interfaces: blood-CSF barrier across arachnoid barrier cell layer, blood-CSF barrier across pial microvessels and outer CSF-brain barrier comprising glial end feet layer/pial surface layer.